Effect of information and communication technology-based smart care services for physical and cognitive functions in older adults living alone: A quasi-experimental study - Du-Ri Kim; Ting-Fu Lai; Minji Sung; Minwoo Jang; Yeo-Kyung Shin; Young jin Ra; Yung Liao; Jong-Hwan Park; Myung-Jun Shin (Elsevier, 2024)
Background: As the global population ages and the number of older adults living alone increases, societies face the responsibility of building new support systems and providing novel forms of care to ensure the independence and happiness of sick or frail older individuals. This quasi-experimental study examined the association between information and communication technology-based smart care services and the physical and cognitive functions of older individuals living alone. Methods: This study used a suite of smart technologies (artificial intelligence speaker, radar sensor, and personalized exercise App.) and interventions tailored to the initial physical functional scores of the participants. A total of 176 participants were recruited and assigned, with 88 participants in the intervention group and 88 in the control group. The short physical performance battery (SPPB), the digit span test (DST), and the Korean mini-mental state examination (K-MMSE) were used to assess participants before and after 12 weeks. Results: No significant differences in gender, age, or educational levels were observed between the intervention and control groups. After adjusting for baseline performance, analysis of covariance revealed that the intervention group exhibited better outcomes in the SPPB five-time chair stand score (adjusted score difference: 0.329; P = 0.044) and the backward DST (adjusted score difference: 0.472; P = 0.007), but had lower score of K-MMSE (adjusted score difference: −0.935; P = 0.021), indicating enhanced lower limb muscle strength and cognitive function in working memory. Conclusion: ICT-based smart care services, combined with personalized exercise interventions, significantly support the physical and cognitive health of solitary older individuals. This approach highlights the potential of integrating smart technology and targeted physical activity to foster the well-being of the aging population living alone.